A modular design method based on TRIZ and AD and its application to cutter changing robot. (July 2021) - Yang, Mei; Xia, Yimin; Jia, Lianhui; Wang, Dujuan; Ji, Zhiyong
Modular design, Axiomatic design (AD) and Theory of inventive problem solving (TRIZ) have been increasingly popularized in concept design of modern mechanical product. Each method has their own advantages and drawbacks. The benefit of modular design is reducing the product design period, and AD has the capability of problem analysis, while TRIZ's expertise is innovative idea generation. According to the complementarity of these three approaches, an innovative and systematic methodology is proposed to design big complex mechanical system. Firstly, the module partition is executed based on scenario decomposition. Then, the behavior attributes of modules are listed to find the design contradiction, including motion form, spatial constraints, and performance requirements. TRIZ tools are employed to deal with the contradictions between behavior attributes. The decomposition and mapping of functional requirements and design parameters are carried out to construct the structural hierarchy of each module. Then, modules are integrated considering the connections between each other. Finally, the operation steps in application scenario are designed in temporal and spatial dimensions. Design of cutter changing robot for shield tunneling machine is taken as an example to validate the feasibility and effectiveness of the proposed method.